2011
DOI: 10.1073/pnas.1017993108
|View full text |Cite
|
Sign up to set email alerts
|

Linking functional diversity and social actor strategies in a framework for interdisciplinary analysis of nature's benefits to society

Abstract: The crucial role of biodiversity in the links between ecosystems and societies has been repeatedly highlighted both as source of wellbeing and as a target of human actions, but not all aspects of biodiversity are equally important to different ecosystem services. Similarly, different social actors have different perceptions of and access to ecosystem services, and therefore, they have different wants and capacities to select directly or indirectly for particular biodiversity and ecosystem characteristics. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
140
0
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(174 citation statements)
references
References 61 publications
1
140
0
23
Order By: Relevance
“…Our study demonstrates that LP is part of an integrated socialecological system where ecological and social-economic drivers interact along gradients of climate and economic development (22). In high-productivity regions, woody-plant cover negatively affects LP mainly through reductions in forage availability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrates that LP is part of an integrated socialecological system where ecological and social-economic drivers interact along gradients of climate and economic development (22). In high-productivity regions, woody-plant cover negatively affects LP mainly through reductions in forage availability.…”
Section: Resultsmentioning
confidence: 99%
“…Ecological factors, including NPP and woody-plant cover, determine potential stocking rates but actual stocking rates are modulated by manager's decisions (22). In some cases, land managers overstock rangelands leading to degradation and desertification (23), whereas in other cases managers understock.…”
mentioning
confidence: 99%
“…Furthermore, stakeholder participation in planning activities is defined as a process in which stakeholders play an active role in determining the research objectives and their effectiveness throughout the entire research process (Bell et al, 2012;Reed, 2008;Schirmer, 2011). Chan et al (2012), Díaz et al (2011) and Nahlik et al (2012) highlight the need for stakeholder integration and the development of interdisciplinary methodological approaches in order to understand mutual connections between natural and social subsystems. The guideline presented in this paper was applied in a regional governance process and revealed that stakeholder engagement, participation, involvement and dialogue is needed at every process phase (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using traits to generate agroecosystem management strategies Previous efforts to integrate functional trait research into ecosystem service assessments have been proposed, but these have stopped short of creating tangible management targets that can be practically implemented by managers [20,39,65]. Farmers do not manage for traits directly, but rather manage agroecosystems by manipulating the abundances and location of species or through physical and chemical manipulation of the agroecosystem (e.g., tillage or fertilization).…”
Section: Traits Across Multiple Trophic Levelsmentioning
confidence: 99%